INTEGRATION OF SUSTAINABLE INNOVATIONS IN AGRI-FOOD TRADE STRATEGIES AND THEIR IMPACT ON CONSUMER - Dukić, Ana; Urošević, Ana; Ilić, Božo; Mihailović, Đorđe (Economics of Agriculture, 2026)
The aim of this paper is to examine the impact of sustainableinnovations in agri-food retail on consumer satisfactionand the moderating role of retail store image. A quantitativesurvey with a structured questionnaire was conducted on381 consumers. Data were analyzed using correlation,multiple regression, and moderation regression analysesin IBM SPSS Statistics. Results show that environmentalsustainability, product and marketing innovationssignificantly affect consumer satisfaction. Findingssuggest that managers can enhance competitiveness andresource efficiency by integrating sustainability intoproduct and marketing innovations, especially for organicand sustainably sourced products. The study introducesnovelty by analyzing retail store image as a moderator,providing insights into interdependent relationships thathave been largely overlooked in existing literature. Thisresearch offers practical implications for strategic decisionmaking in agri-food retail, promoting sustainable practicesand healthy consumer choices.